Prevalence and characterization of hypoadrenocorticism in dogs with signs of chronic gastrointestinal disease: A multicenter study. (23rd June 2020) - Hauck, Christina; Schmitz, Silke S.; Burgener, Iwan A.; Wehner, Astrid; Neiger, Reto; Kohn, Barbara; Rieker, Thomas; Reese, Sven; Unterer, Stefan
Abstract: Background: Dogs with hypoadrenocorticism (HA) frequently show signs of gastrointestinal disease (SGD). The prevalence of dogs presented for chronic SGD with HA is unknown. Objectives: The aims of this study were to determine the prevalence of HA in dogs with chronic SGD and to identify clinical and laboratory variables for HA in this population. Animals: One hundred fifty‐one dogs with chronic SGD. Methods: In this multicentered prevalence study a standardized workup was performed in prospectively enrolled dogs with SGD > 3 weeks duration. Basal serum cortisol concentration was measured in every dog with ACTH stimulation test (ACTHST) if basal serum cortisol concentration was <3 μg/dL. Results: Basal serum cortisol concentration was <3 μg/dL in 80/151 (53%) dogs, <2 μg/dL in 42/151 (28%) dogs, and < 1 μg/dL in 9/151 (6%) dogs. In 6/151 dogs HA was diagnosed based on ACTHST (stimulated serum cortisol concentration < 2 μg/dL), a prevalence of 4%. There was no difference in history, physical examination, and laboratory variables between dogs with HA and those with other causes of chronic SGD. In 4/6 dogs with HA, there was melena or hematochezia indicating gastrointestinal blood loss. Hyperkalemia, hyponatremia, or both was not observed in any dog. Conclusion and Clinical Importance: The prevalence of HA among dogs with chronic SGD is higher than in the general population. Based on these results, testing adrenal function should be performed as a standard screening test in dogs with chronic SGD to differentiate between HA and chronic enteropathies.